Parking Management System Prototype Using Multiplatform Based NodeMCU - Akhriana, Asmah; Husain, Husain; Aisa, Sitti; Arifin, Suci Ramadhani; Nur, Muhammad Muhaimin; Sulihin, Hafsah (Program Studi Teknik Elektro Universitas Khairun, 2024)
Currently, the parking management implemented in several public places has not been managed properly, resulting in a buildup of vehicles and it is difficult for many vehicles to find a parking space. The Maspul Jaya boarding house as an example has challenges in managing parking because there are a large number of residents with 60 rooms and a limited number of parking lots, which means residents often have difficulty getting a parking space in the boarding house area. This research aims to design a prototype parking management system using NodeMCU and RFID card technology as a replacement for room number stickers on Maspul Jaya Boarding House residents' vehicles with a multiplatform Android and iOS-based application connected to the network. The data obtained will be processed by the microcontroller and sent to the database server and then displayed in the application. The application testing method used is Blackbox and direct testing of the system hardware. The results of this research are that at the entrance gate, residents can enter through the parking barrier if the driver brings the vehicle close to the infrared proximity sensor, the RFID card is registered, the card status is active and the driver is not detected as being parked. When all conditions are met, the servo as the entrance parking gate will open, and the opposite condition will occur on the side of the exit gate. The maximum reading distance between the object and the sensor is 8 cm and RFID cards can be read at a maximum distance of 3 cm. Apart from that, the results of black box testing on the input-output of this application function well and are free from errors so that monitoring can be carried out via the application on data related to empty parking slots and the history of vehicles that have been parked using both the Android and iOS platforms. With this system, parking management at the Maspul Jaya boarding house will become more organized and efficient.Â Â